Evaluation of the effects of spray technology and volume rate on the control of grape berry moth in mountain viticulture - Michael, Costas; Gil, Emilio; Gallart, Montserrat; Stavrinides, Menelaos (My University, 2021)
The current work evaluated spray coverage and pest control effectiveness against the grape berry moth (Lobesia botrana) by two different spray technologies and volume rates: A spray gun (high-volume sprayer—HVS) calibrated at 1000 L ha−1 and a conventional orchard sprayer calibrated at 500 L ha−1 (OS500) or 250 L ha−1 (OS250). Experiments were carried out in three different grape varieties over two years in mountain vineyards on the Mediterranean island of Cyprus. The median coverage for HVS remained above 80% for all three varieties, while that for OS500 ranged from 26% to 56%, and that for OS250 from 18% to 37%. Infestation by the grape berry moth varied from about 2.5% for Palomino, to 8% for Carignan and 3.2% for Xynisteri. Infestation in sprayed plots remained below 1.8% for all treatments, varieties and study years. Although infestation levels in OS250 were not different than the control in two varieties, the infestation levels among sprayer treatments did not differ by more than one percentage point. The current work suggests that lowering application volume and pesticide amount to 50% or more, in some cases, provides adequate control and represents an effective option for reducing pesticide use in vineyards.
Keywords: Vineyards; Pest control; Pesticide use; Sustainable use of pesticides directive; Farm to Fork Strategy